Extraction-photometric determination of osmium using quaternary water-thiopyrine-trichloroacetic and orthophosphoric acid system - Egorova, L.S.; Leites, E.A. (KSU Publ., 2020)
The article is devoted to the extraction-photometric determination of osmium. The aim was to modify the well known extraction-photometric determination of osmium by replacing chloroform, used as an organic solvent in a traditional extraction system, on to water, which is the only liquid component in the layering system. This made it possible to eliminate the toxic organic solvent from the system. The optimal conditions for the osmium extraction were selected, taking with the fact that the consumption of thiopyrine, as an expensive reagent, should be minimal. The results of the developed methodology for determining microgram amounts of osmium with thiopyrine were presented by the example of a model mixture corresponding to the composition of a platinum sponge. The interfering effect of Al (III), B (III), Bi (III), Fe (III), Au (III), Ir (II), Cd (II), Co (II), Ca (II), Si (IV), Mg (II), Mn (II), Cu (II), Mo (VI), As (V), Ni (II), Sn (IV), Pd (II), Rh (II), Pb (II), Ag (I), Sb (III), Te (IV), Cr (III), Zn (II) contained in a platinum sponge was investigated. The interfering effect of copper has been established, which is eliminated by masking with ascorbic acid.
«Су – тиопирин – трихлорацетикалық жəне ортофосфор қышқылы» төрттік жүйесінің көмегімен осмийді экстракциялық-фотометриялық анықтау
Экстракционно-фотометрическое определение осмия с помощью четверной системы «вода – тиопирин – трихлоруксусная и ортофосфорная кислоты»
Keywords: osmium; hiopyrine; extraction-photometric determination; platinum sponge; complexation; synthesis of drugs; cortisone